Ultrabright plasmonic fluor nanolabel-enabled detection of a urinary ER stress biomarker in autosomal dominant tubulointerstitial kidney disease - Kim, Yeawon; Wang, Zheyu; Li, Chuang; Kidd, Kendrah; Wang, Yixuan; Johnson, Bryce G; Kmoch, Stanislav; Morrissey, Jeremiah J; Bleyer, Anthony J; Duffield, Jeremy S; Singamaneni, Srikanth; Chen, Ying Maggie (American journal of physiology. Renal physiology, 2021)
Autosomal dominant tubulointerstitial kidney disease (ADTKD)-uromodulin (UMOD) is the most common nonpolycystic genetic kidney disease, but it remains unrecognized due to its clinical heterogeneity and lack of screening test. Moreover, the fact that the clinical feature is a poor predictor of disease outcome further highlights the need for the development of mechanistic biomarkers in ADTKD. However, low abundant urinary proteins secreted by thick ascending limb cells, where UMOD is synthesized, have posed a challenge for the detection of biomarkers in ADTKD-UMOD. In the CRISPR/Cas9-generated murine model and patients with ADTKD-UMOD, we found that immunoglobulin heavy chain-binding protein (BiP), an endoplasmic reticulum chaperone, was exclusively upregulated by mutant UMOD in the thick ascending limb and easily detected by Western blot analysis in the urine at an early stage of disease. However, even the most sensitive ELISA failed to detect urinary BiP in affected individuals. We therefore developed an ultrasensitive, plasmon-enhanced fluorescence-linked immunosorbent assay (p-FLISA) to quantify urinary BiP concentration by harnessing the newly invented ultrabright fluorescent nanoconstruct, termed "plasmonic Fluor." p-FLISA demonstrated that urinary BiP excretion was significantly elevated in patients with ADTKD-UMOD compared with unaffected controls, which may have potential utility in risk stratification, disease activity monitoring, disease progression prediction, and guidance of endoplasmic reticulum-targeted therapies in ADTKD.NEW & NOTEWORTHY Autosomal dominant tubulointerstitial kidney disease (ADTKD)-uromodulin (UMOD) is an underdiagnosed cause of chronic kidney disease (CKD). Lack of ultrasensitive bioanalytical tools has hindered the discovery of low abundant urinary biomarkers in ADTKD. Here, we developed an ultrasensitive plasmon-enhanced fluorescence-linked immunosorbent assay (p-FLISA). p-FLISA demonstrated that secreted immunoglobulin heavy chain-binding protein is an early urinary endoplasmic reticulum stress biomarker in ADTKD-UMOD, which will be valuable in monitoring disease progression and the treatment response in ADTKD.
Keywords: biologické markery; chaperon endoplazmatického retikula BiP; Biomarkers; uromodulin; biomarker; intersticiální nefritida; Uromodulin; autosomal dominant tubulointerstitial kidney disease; Heat-Shock Proteins; endoplasmic reticulum stress; stres endoplazmatického retikula; Nephritis, Interstitial; Endoplasmic Reticulum Chaperone BiP; Animals; lidé; imunosorpční techniky; plasmon-enhanced fluorescence-linked immunosorbent assay; Humans; zvířata; myši; Immunosorbent Techniques; Endoplasmic Reticulum Stress; Mice; proteiny teplotního šoku